Pelatihan Pembuatan Benda Sederhana Menggunakan Printer 3D Sebagai Peningkatan Kemampuan Guru dan Murid di Manado Independent School (MIS) Kabupaten Minahasa Utara: Training on Making Simple Objects Using 3D Printers as Improving the Ability of Teachers and Students at Manado Independent School - Neyland, Johan S.C.; Rembet, Michael E.; Rondonuwu, Irvan R. (Vivabio: Jurnal Pengabdian Multidisiplin, 2025)
ABSTRACT The Community Partnership Program (PKM) partners are teachers and students from the Manado Independent School High School in North Minahasa Regency which is economically unproductive. This school partner already has a 3D printer which is still standard, namely the Axis type which still moves based on the XYZ axis, also because they don't know the operating SOP for the 3D printer, this has resulted in damage which has not yet been repaired. The Unsrat PKM team will provide training in making simple objects and assistance as well as implementing the right technology for these partners, one way is to introduce and to partners the tools or machines that have been developed, namely the Delta model 3D Printer which moves based on the motor on the printer arm. The tool developed has a practical design that can be changed in terms of dimensions and function according to the specific needs of partners and the production cost per unit of this tool is also relatively cheap. Assistance is also provided in terms of SOPs for operating, servicing and repairing 3D printer equipment so that this tool can be used effectively and maximally in improving the abilities of teachers and students in daily school activities. The result of this PKM activity is that SMA partners have begun to understand the process of operating a 3D printer and simple handling if the printer has problems. ABSTRAK Mitra Progran Kemitraan Masyarakat (PKM) ini adalah guru dan murid dari sekolah SMA Manado Independent School di Kabupaten Minahasa Utara yang secara ekonomi tidak produktif. Mitra sekolah ini telah memiliki alat printer 3D yang masih standar yaitu tipe Axis yang masih bergerak berdasarkan sumbu XYZ, juga akibat mereka belum mengetahui SOP pengoperasian dari printer 3D tersebut mengakibatkan kerusakan yang sampai saat ini belum dapat diperbaiki. Tim PKM Unsrat akan memberikan pelatihan pembuatan benda sederhana dan pendampingan sekaligus untuk menerapan teknologi yang tepat bagi mitra tersebut, salah satu cara adalah memperkenalkan dan kepada mitra alat atau mesin  yang telah dikembangkan yaitu 3D Printer model Delta yang bergerak berdasarkan motor yang ada pada lengan printer. Alat yang dikembangkan ini memiliki rancangan yang praktis yang secara dimensi dan secara fungsi dapat dirubah sesuai dengan kebutuhan spesifik dari mitra juga biaya produksi per satu unit alat ini juga relatif murah. Juga dilakukan pendampingan dalam hal SOP dari pengoperasian, servis dan perbaikan alat 3D printer agar supaya alat ini dapat dipergunakan dengan efektif dan maksimal dalam meningkatkan kemampuan guru dan murid pada kegiatan sekolah sehari-hari. Hasil kegiatan PKM ini adalah mitra SMA sudah mulai memahami bagaimana proses pengoperasian printer 3D dan penanganan sederhana jika printer bermasalah.